Scale without Mass: Permanent Establishments in the Digital Economy - Ocampo, Andrés Felipe Ramírez (Revista de Direito Tributário Internacional Atual, 2019)
This paper contains an overview of the currently existing guidelines on permanent establishments as set forth in the Commentary to the OECD Model Tax Convention on Income and on Capital and their applicability to the digital economy. These insights are used to compare current OECD standards with the Proposal for a council directive laying down rules relating to the corporate taxation of a significant digital presence (2018/0072 (CNS)) issued in March 2018, for discussion in the context of the European Union. The conclusion analyses the applicability and effects of these considerations for developing countries.